Accounting for the Effects of Oil Prices on Exchange Rate in Nigeria: Empirical Evidence from Linear and Non-Linear ARDL Models - Naeem, Nasir; Sa’ad, Suleiman; Sanusi, Aliyu Rafindadi; Usman, Ali Baba (European Scientific Journal, ESJ, 2023)
This study empirically examines the impact oil prices on the exchange rate in Nigeria. Time series annual dataset spanning 1980 to 2018 was estimated using the linear and nonlinear ARDL model developed by Pesaran and Shin, (1998) & Pesaran, et al. (2001) and Shin, et al. (2014); where oil prices, nominal exchange rate, interest rate, and oil revenue serves as the variables for analysis. From the result of the linear-ARDL models both the long run and short-run revealed that oil price has positive and significant impact on exchange rate. Similarly, the nonlinear model also revealed that, both in the long run and short-run, the depreciating effect of a fall in oil price is stronger than an appreciating effect of a arise in oil price of an equal magnitude. This, we argue, reflects the dependency of the economy on oil. One policy implication of this finding is that stability of oil prices and oil revenue is critical for the stability of the domestic currency and, hence, prices. It is, therefore, recommended that authorities should focus on resolving the production difficulties in the Nigeria’s oil industry as a means of reducing the current revenue volatility.